The role of the Russian Federation in the formation of a single scientific and educational space of the Eurasian Economic Union - T.V. Lebedeva (Векторы благополучия: экономика и социум)
In the current geopolitical conditions, when the Russian Federation is forced to exist under Western sanctions, more and more attention in foreign policy is paid to establishing cooperation with friendly countries, primarily with the member states of the Eurasian Economic Union (EAEU). One of the most important areas of humanitarian cooperation within the EAEU is the formation of a single scientific and educational space. The article is devoted to identifying the role of the Russian Federation in the initiation and development of this fundamental process, since only the availability of highly qualified personnel can ensure high economic growth of each member state of the integration association individually and the economic union as a whole. The development of the basic principles of interaction in the Eurasian scientific and educational space has been taking place "in small steps" for almost 10 years. The scientific review presented in the article contains an analysis of modern initiatives and practical steps taken to form a single scientific and educational environment in the EAEU. It is noted that the Russian Federation, which chaired the EAEU in 2023, put forward a number of initiatives to intensify cooperation between educational systems in the Eurasian space. Based on the research conducted using statistical, graphical and other methods, the article identifies 11 reasons that hinder the intensification of this process. Particular attention is paid to the differences in the features of the functioning of the higher education systems of the EAEU member states, and to the adherence of some of them to the principles of the Bologna system. The low level of academic mobility of students and teachers between universities in the Eurasian space, as well as the reduction in the volume of educational migration between the EAEU member states in recent years, are of concern. Therefore, the Russian Federation, with the most powerful system of personnel training in the EAEU, should continue to put forward initiatives that will contribute to the earliest possible formation of a single scientific and educational space.